Methods for policy research : taking socially responsible action - Majchrzak, Ann; Markus, M. Lynne (Thousand Oaks, Calif. : SAGE Publications, Inc., 2014)
Methods for Policy Research, Second Edition, by Ann Majchrzak and M. Lynne Markus, is a book about responsible and evidence-based decision making written for those interested in improving the decisions that affect people's lives. It describes how to define policy research questions so that evidence can be applied to them, how to find and synthesize existing evidence, how to generate new evidence if needed, how to make acceptable recommendations that can solve policy problems without negative side effects, and how to describe evidence and recommendations in a manner that changes minds. The suggestions made throughout the book are based on the fundamental belief that evidence-based decision making is superior to decisions based purely on opinion, intuition, and emotion.
Foreword -- Preface -- Acknowledgements -- About the authors -- chapter 1. Make a difference with policy research -- chapter 2. Launch the policy research process -- chapter 3. Synthesize existing evidence -- chapter 4. Obtain new evidence -- chapter 5. Design policy recommendations -- chapter 6. Expand stakeholder engagement -- chapter 7. Reflect on the policy research voyage -- References -- Index.
Includes bibliographical references (pages 149-151) and index.
Description based on MARC record for print version.
Keywords: elektronické knihy; electronic books; Policy sciences -- Research